2011
DOI: 10.1039/c1dt10578g
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic gold(i)-bearing dendrimers from alkyne precursors

Abstract: A series of four dendrimers end-functionalized with gold(I) has been prepared from alkyne-terminated precursors and (tricyclohexylphosphine)gold(I) azide. Isolated yields range from 84-89%, based on gold. The first-generation dendrimer is cytotoxic toward 3T3 mouse fibroblast cells. Apoptosis ensues within 6 h of treatment with gold(I).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 15 publications
(6 reference statements)
0
28
0
Order By: Relevance
“…[2][3][4] Others [5][6][7] extended iClick to include the already prevalent [8][9] cycloaddition of an organic substrate to either a metal-azide or metal-acetylide. 7,[10][11][12][13][14][15][16][17][18][19][20][21] Important to this work, Gray et al 22 demonstrated that gold-acetylides and gold-azides will undergo cycloaddition to their organic counterparts. Despite the fact that several transition metals other than Cu(I) catalyze the azide-alkyne cycloaddition, including ruthenium, silver, and iridium, [23][24][25][26] it became apparent that not all metal-acetylide/azide species will participate in the iClick cycloaddition.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Others [5][6][7] extended iClick to include the already prevalent [8][9] cycloaddition of an organic substrate to either a metal-azide or metal-acetylide. 7,[10][11][12][13][14][15][16][17][18][19][20][21] Important to this work, Gray et al 22 demonstrated that gold-acetylides and gold-azides will undergo cycloaddition to their organic counterparts. Despite the fact that several transition metals other than Cu(I) catalyze the azide-alkyne cycloaddition, including ruthenium, silver, and iridium, [23][24][25][26] it became apparent that not all metal-acetylide/azide species will participate in the iClick cycloaddition.…”
Section: Introductionmentioning
confidence: 99%
“…6 Critical in the pursuit of building complexity is the precise control of bond forming events and is particularly exemplified by the Cu I catalyzed azide-alkyne cycloaddition reaction (CuAAC). Others [11][12][13] have broadened the iClick concept to include the cycloaddition of organic substrates to either a metal-azide or metal-acetylide (M; Scheme 1), which are already rather prevalent reactions, [13][14][15][16][17][18][19][20][21][22][23][24][25] and the subject of reviews. The metal-azide/metal-acetylide cycloaddition (M-M′) was given the term inorganic click (iClick) as a distinguishing feature that calls attention to chemistry occurring within the coordination sphere of a metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…[447,449] Gold-peptide bioconjugates overcome cisplatin resistance in a cancer cell line. [449] An allylpalladium azide which undergoes 1,3-dipolar cycloaddition with alkynes is proposed as key intermediate in the www.zaac.wiley-vch.de [458] three component-coupling reaction of activated alkynes, allyl-methyl carbonate and trimethylsilyl azide for the regiospecific synthesis of 2-allyl-1,2,3-triazoles.…”
Section: )mentioning
confidence: 99%
“…[427] Recently, a series of interesting gold complexes with carbon-bound triazolate ligands has been obtained by Gray and by Metzler-Nolte and co-workers from reactions of phosphinegold(I) azides with terminal organic alkynes (Equation (13)). [446][447][448][449] In the place of phosphine ligands, also N-heterocyclic carbenes have been used, and a series of functionalized alkynes has been introduced in these reactions. [448] Until now the mechanism of formation of the C-bound triazolate has not been established.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation